From high rise to coast: Revitalizing Ribeira da Barcarena - Matt Kondolf; Kristen Podolak; Andrea Gaffney (University of California, Institute of Urban and Regional Development (IURD), 2010)
The Lisbon metropolitan region has grown rapidly in population since 1970, due largely to the immigration of people from former Portuguese colonies in Africa and from rural areas of the country in pursuit of higher living standards. Much of this population growth was accommodated clustered high-rise apartment blocks (many unpermitted) in the region west of Lisbon, in the municipalities Oeiras, Cascais, Sintra, and Amadora. These developments were largely unplanned, often did not provide for sewage treatment, and lack adequate mass transit or urban amenities such as parks and other open spaces. Moreover, because the main transport axes run east-west, it is difficult for residents of these apartment blocks to go the relatively short distance southward to the coast (e.g., only 10 km from Cacém to the coast). This region is drained by a set of subparallel streams (each draining about 20-50 km2), flowing roughly north-south through deeply incised valleys to debouch into the Atlantic between Lisbon and Cascais. With rapid urbanization peak runoff has increased, resulting from larger impervious surfaces and sewage from illegal housing settlements. Many reaches have been canalized within concrete walls to increase flood capacity, eliminating physical habitat complexity, and reducing amenity and recreational values. However, the urbanization has occurred mostly on uplands, leaving the bottomlands of the incised stream valleys in many reaches surprisingly unaltered. For decades, these drainages were largely neglected, managed mostly to convey floodwaters, although in some reaches there was strong informal use of the stream corridor and floodplains (such as garden plots). The Water Framework Directive (WFD) adopted by the EU Parliament (2000), has motivated extension and improvement of the regional sewer network to improve water quality. The WFD requires that all water bodies in member states achieve Good Ecological Status by 2015, defined in terms of hydromorphological, biological, and physico-chemical quality elements of stream reaches, based on characteristics documented at reference sites. Located 15 km west of Lisbon, Ribeira da Barcarena-Jardas drains a 35 km2 catchment, whose uppermost reaches are forested, but otherwise alternates between urbanization and remnant agricultural and open-space uses. With improved sewage treatment and water quality, there is strong potential to preserve and restore ecological functions, consistent with goals of good ecological status. As illustrated by the successful urban stream project in Cacém, there is tremendous potential for the stream corridor to provide parkland for the dense urban settlements. Through GIS analysis of remotely-sensed data, and field surveys of water quality, habitat structure, riparian vegetation, and fish populations, an interdisciplinary workshop of graduate students from Berkeley and Lisbon analyzed potential opportunities to enhance ecological values and human access along the stream. Our analysis indicated that implementation of stormwater management strategies via relatively unobtrusive retrofits of small open bits of urban land and floodplain within the catchment could mitigate many of the negative hydrologic effects of urbanization. By virtue of its linear nature, the stream corridors could provide pedestrian and bicycle connections from population centers (now under-served by parklands) to cultural features and to coastal beaches and trails. A trail could inspire similar efforts on neighboring, parallel basins that have undergone similar urbanization pressures and face similar challenges in providing underserved urban populations with access to creation and contact with nature
Keywords: 330; stream restoration; Ribeira Barcarena; Ribeira Jardas; water framework directive; Lisbon metropolitan region; linear trail; stream corridor